Opportunities for Increasing Brand Equity by Managing Its Social Media Communications - Murzova, Mariana (Research Papers, 2024)
Proper management of brand value components is an essential part of building this intangible asset and thus forming protective barriers to competitors and improving its status. In this regard, increasing brand equity should be the main marketing goal of each company. Its achievement goes through building favorable associations and forming positive feelings among target customers. Digital marketing communications are the easiest, fastest and most effective tool for this.
Keywords: Marketing communications; Brand equity; Social media; Brand